Post-resuscitation pneumothorax: retrospective analysis of incidence, risk factors and outcome-relevance - Daniel Auinger; David Hötzer; Paul Zajic; Simon Orlob; Stefan Heschl; Stephanie Fida; Philipp Zoidl; Gabriel Honnef; Herwig Friedl; Freyja-Maria Smolle-Jüttner; Gerhard Prause (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Background Pneumothorax may occur as a complication of cardiopulmonary resuscitation (CPR) and could pose a potentially life-threatening condition. In this study we sought to investigate the incidence of pneumothorax following CPR for out-of-hospital cardiac arrest (OHCA), identify possible risk factors, and elucidate its association with outcomes. Methods This study was a retrospective data analysis of patients hospitalized following CPR for OHCA. We included cases from 1st March 2014 to 31st December 2021 which were attended by teams of the physician staffed ambulance based at the University Medical Centre Graz, Austria. Chest imaging after CPR was reviewed to assess whether pneumothorax was present or not. Logistic regression analysis was performed to identify factors for the development of pneumothorax relevant and to assess its association with outcomes [survival to hospital discharge and cerebral performance category (CPC)]. Results Pneumothorax following CPR was found in 26 out of 237 included cases (11.0%). History of obstructive lung disease was significantly associated with presence of pneumothorax after CPR. This subgroup of patients (n = 61) showed a pneumothorax rate of 23.0%. Pneumothorax was not identified as a relevant factor to predict survival to hospital discharge or favourable neurological outcome (CPC1 + 2). Conclusions Pneumothorax may be present in greater than one in ten patients hospitalized after CPR for OHCA. Pre-existent obstructive pulmonary disease seems to be a relevant risk factor for development of post-CPR pneumothorax. ClinicalTrials.gov ID: NCT06182007 (retrospectively registered). Trial Registration: NCT06182007 (retrospectively registered)